A Pharmacist's Reflection on the Symposium's OTC Hearing Aid Implementation Panel - Mook, Hailey (Seminars in Hearing, 2025)
Implementation of over-the-counter (OTC) hearing aid sales can take many forms. The OTC Hearing Aid and Self-Care Symposium included one panel of speakers who addressed considerations for implementation from the perspectives of pharmacists, audiologists, and consumers. This article, written by the panel moderator, offers an overview of implementation options and issues addressed by the speakers and a pharmacist's perspective on the need for interprofessional collaboration.
Keywords: OTC hearing aids; implementation; audiologist